Edaravone Improved Behavioral Abnormalities, Alleviated Oxidative Stress Inflammation, and Metabolic Homeostasis Pathways in Depression - Montazeri, Sina; Bijani, Soroush; Anoush, Mahdieh; Sharafi, Ali; Kalantari-Hesari, Ali; Hosseini, Mir-Jamal (Depression and Anxiety, 2023)
Depression is one of the main factors affecting our daily performance. Among many putative compounds with effect on behavioral and pathophysiological alterations in depression, edaravone (EDV) demonstrates antioxidant and free radical scavenging properties. To investigate possible antidepressive and anxiolytic-like effects of EDV, Wistar rats were randomly divided into six groups: (1) control; (2) EDV (6 mg/kg); (3) post weaning social isolation (PWSI); (4) PWSI+EDV (1.5 mg/kg); (5) PWSI+EDV (3 mg/kg); and (6) PWSI+EDV (6 mg/kg). After the series of behavioral tests, animals were sacrificed, and their hippocampi were dissected for further biochemical and gene expression assays. Our results showed that treatment with 3 and 6 mg/kg EDV after social isolation would improve anxiety, depressive and anhedonic-like behavior in OFT, EPM, FST, and splash tests. In addition, treatment at the aforementioned doses achieved to recover total cellular antioxidant and GSH level. These effects were accompanied with the suppressive effect of EDV on MDA and PCO levels. EDV treatment also modulated the expression of AMPK, Tlr-4, BDNF, nNOS, and iNOS genes. The treatment with 3 and 6 mg/kg EDV would lead to the recovery of behavioral impairments, cellular free radical surge that could be in correlation with the effect of this substance on immune system response, improved energy production system, and more efficacy in the recovery of neural tissue. In conclusion, EDV ameliorates depressive-like disorder by modulating neuroinflammation, energy production, and neural tissue recovery.